Method for taking into account the phase transition in biological tissue during computer-aided simulation of cryodestruction process - Anatychuk, L.I.; Kobylianskyi, R.R.; Fedoriv, R.V. (Journal of Thermoelectricity, 2019)
The paper presents a method for taking into account the phase transition in biological tissue during computer-aided simulation of cryodestruction process. The physical, mathematical and computer models of biological tissue are constructed with regard to thermophysical processes, blood circulation, heat transfer, metabolic processes and the phase transition. As an example, we consider the case when there is a cooling element on the surface of biological tissue at a temperature of -50 ° C. The temperature and heat flux distributions in biological tissue are determined in cooling mode. The results obtained make it possible to predict the depth of freezing of biological tissue at a given temperature exposure. Bibl. 28, Fig. 7, Table. 1.